x+22+4x=-46-4x-49

Simple and best practice solution for x+22+4x=-46-4x-49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+22+4x=-46-4x-49 equation:


Simplifying
x + 22 + 4x = -46 + -4x + -49

Reorder the terms:
22 + x + 4x = -46 + -4x + -49

Combine like terms: x + 4x = 5x
22 + 5x = -46 + -4x + -49

Reorder the terms:
22 + 5x = -46 + -49 + -4x

Combine like terms: -46 + -49 = -95
22 + 5x = -95 + -4x

Solving
22 + 5x = -95 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
22 + 5x + 4x = -95 + -4x + 4x

Combine like terms: 5x + 4x = 9x
22 + 9x = -95 + -4x + 4x

Combine like terms: -4x + 4x = 0
22 + 9x = -95 + 0
22 + 9x = -95

Add '-22' to each side of the equation.
22 + -22 + 9x = -95 + -22

Combine like terms: 22 + -22 = 0
0 + 9x = -95 + -22
9x = -95 + -22

Combine like terms: -95 + -22 = -117
9x = -117

Divide each side by '9'.
x = -13

Simplifying
x = -13

See similar equations:

| 8x+5=6(x+6) | | 10a-3a= | | b-1=-4 | | 6x+39=14x-23 | | 21-r=7 | | 5(x-1)+2x=7(x-3)+4 | | x-12=-41 | | 24-6x=15+3x | | 4-5y=6(3-2y) | | 8=19+x | | 3(2x-3)+11=8 | | 3x+36=8-4x | | -6=k-11 | | 5x-3=6x+9 | | 3(6-0.0033333333y)+y=18 | | 3=3a+18 | | 11x-14=107 | | 11x=97 | | 3(x+9)+129=180 | | 4(3u+5)=8u+14 | | 8(a+b)+3z=-9 | | -13+v=-28 | | 18*x=2*18+2(x) | | 4x-3-x=-18+6x | | 3(d+4)-11=321-23 | | 3(3t-4)+4(6-t)=18 | | 10x+9+6x=-8+8x+1 | | 2x+15+6x=10+5x-7 | | 7+2x+4x=57+x | | -2x=60 | | 7t+5(1-4t)= | | (2x+6)*(4-x)=0 |

Equations solver categories